Analyzing brand identity in the sustainable skincare industry: Study case of Keina Beauty - I Gusti Ayu Komang Triana Gyshela; Eko Ganiarto (Universitas Pendidikan Nasional, 2025)
In the competitive beauty industry, effective branding is critical for differentiation and long-term success, especially as consumers increasingly demand sustainable and ethical products. This study examines how Keina Beauty, an eco-friendly skincare brand, can enhance its brand identity to gain a competitive advantage in the beauty industry. The research question focuses on identifying the strategic modifications required to strengthen branding and better align with target customer segments. A qualitative approach was employed, integrating analyses using frameworks such as PESTLE, Porter’s Five Forces, Value Chain, SWOT, Cause and Effect Diagrams, and Business Model Canvas. The results reveal that inconsistent branding, misaligned customer segmentation, and operational inefficiencies are critical challenges facing the company. These findings indicate that the lack of a unified brand identity and strategic digital marketing hampers consumer engagement and market differentiation. The discussion highlights the potential benefits of standardizing visual elements, refining digital and influencer marketing strategies, and enhancing customer service practices to create a coherent and appealing brand image. Conclusively, by implementing targeted strategies to streamline brand elements and improve customer interactions, Keina Beauty can secure sustainable growth and strengthen its market position in a competitive environment.